Estimation of heart and respiratory rates using pulse oximeters - Yap, Felicia Lii Wen (2017)
In this report, algorithm was created to estimate heart rate and respiratory rate using photoplethysmogram (PPG). PPG was acquired from fingertip of human body using pulse sensor amped. The PPG acquired from pulse sensor amped was recorded and save for further processing using MATLAB. PPG signal undergo pre-processing stage which include the removal of DC component to have a better waveform for future analysis. To estimate the respiratory rate, three respiratory induced variations which are frequency, amplitude and intensity are extracted from PPG. All three respiratory induced variations are analysed using Fast Fourier Transform (FFT) to get the frequency spectrum of the respiratory induced variations. Respiratory rate can be estimate from the frequency spectrum. Heart rate can be estimate by performing FFT on PPG. From the PPG frequency spectrum, the highest peak value that falls within the heart rate frequency band which is around 0.6Hz to 5Hz is recorded to calculate for heart rate.